Sphingosine kinase 2 suppresses neutrophil responses to promote viral persistence while attenuating immune pathology - Vijayamahantesh, Vijayamahantesh; He, Ying; Jiang, Lei; Huerter, Hailey; Jung, Kwang Il; McKenna, Savannah; Studstill, Caleb J.; Allen, Lee-Ann H.; Nistala, Ravi; Xu, Dong; Hahm, Bumsuk (Frontiers in Immunology, 2026)
Chronic viral infections often suppress immune cell functions, which helps restrict immune pathology but leads to viral persistence. However, the underlying mechanisms are not completely understood. We recently found that sphingosine kinase 2 (SphK2)-deficient (Sphk2−/−) mice succumb to lymphocytic choriomeningitis virus (LCMV) infection due to immune pathology. In addition to heightened T cell immunity, a notable increase in neutrophil numbers was observed in LCMV-infected Sphk2−/− mice. Depletion of neutrophils increased the viability of virus-infected Sphk2−/− mice, supporting the role of SphK2-deficient neutrophils in viral immune pathogenesis. Furthermore, SphK2-deficient neutrophils expressed lower levels of the immunosuppressive marker CD244 during infection. Importantly, adoptively transferred SphK2-deficient neutrophils demonstrated intrinsic regulation of CD244 and improved virus-specific T cell responses, resulting in a diminished viral burden. Transcriptomic analysis revealed an increased expression of pro-inflammatory and antiviral genes in SphK2-deficient neutrophils. These results indicate that SphK2 promotes suppressive neutrophil responses and regulates neutrophil-associated immune pathology during persistent infections. Our findings may help in the design of new immunotherapeutics to control chronic viral diseases.